KARAKTERISTIK DAN GENESA BATUAN ASAL LATERIT NIKEL SERTA HUBUNGANNYA TERHADAP KELIMPAHAN SKANDIUM DAERAH PULAU PAKAL - HALMAHERA TIMUR - Rachmanto, Hendrata
The Halmahera Islands, in the eastern and central parts, is an area with lithology complex composition of ultrabasic rocks which contains ultramafic rocks that have the potential to produce mineralisation in the form of nickel laterites. Nickel laterites in the study area are located on Pakal Island, a nickel mine owned by PT Antam Tbk. Research on the relationship between ultramafic rocks and cobalt (Co) characteristics in nickel laterite deposits in the Pakal Island area aims to analyse the type of rock of origin that is dominant to cobalt enrichment, and identify the cobalt characteristics of nickel laterite deposits in the study area by identifying the types of minerals associated with cobalt (Co) enrichment in all laterite zones and, determining the type of cobalt (Co) deposits in ultramafic rocks of dunite, harzburgite and serpentinite types. Analytical methods in this study used petrographic analysis and XRD (X-Ray Diffraction) analysis, geochemical analysis using XRF (X-Ray Fluoresence) analysis method. Sufficient sampling data were statistically analysed using histograms and scatter diagrams. The results of the study of the relationship between ultramafic rocks and cobalt (Co) characteristics in nickel laterite deposits in the Pakal Island area show that cobalt concentrations vary along the profile, with the highest enrichment generally occurring in the limonite zone with serpentinite bedrock having the highest grade with an average grade of 0.229% with a limonite zoning thickness of ± 2 metres, while dunite bedrock has a high grade with an average grade of 0.212% with a limonite zoning thickness of ± 10 metres, thus concluding that the dunite rock lithology has good economic potential for further study, especially in the limonite zone compared to harzburgite and serpentinite rock lithologies in the Pakal Island area. dunite rock lithology has better economic potential for further study, especially in the limonite zone compared to harzburgite and serpentinite rock lithologies in the Pakal Island area.